Rat perivascular adipose tissue microvasculature revealed by tissue clearing - Watts, Stephanie W.; Flood, Emma; Gulbransen, Brian D.; Jackson, William F. (Frontiers in Physiology, 2025)
Perivascular adipose tissue (PVAT) surrounds the majority of blood vessels and plays diverse roles in vascular and metabolic functions. The hormonal and lipid exchange functions of PVAT require access to blood vessels. However, the microvascular supply of PVAT, especially in rats, remains enigmatic due to technical restraints involved in imaging fat depots. Therefore, we developed and validated an approach to visualize the microvasculature of PVAT in rats. In this study, we report a stepwise protocol as a method to clear and visualize the microvasculature of the thoracic aortic PVAT in the Dahl salt-sensitive (SS) rat. Blood vessels are first traced in anesthetized rats using Lycopersicon esculentum (tomato) lectin DyLight 649 (Lectin 649). The dissected aorta with intact PVAT is then subjected to a stepwise clearing protocol over 12 days, followed by imaging on a Nikon confocal microscope. Images were stitched together to visualize cross sections of the whole vessels. The microvasculature of aortic PVAT is present and profoundly dense, and it is similar in the ventral and lateral lobes of aortic PVAT. This developed method is adoptable and adaptable to other PVATs in rats.